Trends in atopic dermatitis-from standard pharmacotherapy to novel drug delivery systems - Souto, Eliana B. (2019)
Atopic dermatitis (AD) is a predominant and deteriorating chronic inflammation of the skin, categorized by robust burning and eczematous lacerations in diverse portions of the body. AD affects about 20% of both offspring and adults worldwide. The pathophysiology of AD combines environmental, hereditary, and immunological aspects, together with skin barrier dysfunction. The procedures used to prevent the disease are the everyday usage of creams to support the restoration of the epidermal barrier. The classical treatments include the use of topical corticosteroids as a first-line therapy, but also calcineurin inhibitors, antihistamines, antibiotics, phototherapy, and also immunosuppressant drugs in severe cases of AD. Topical drug delivery to deeper skin layers is a difficult task due to the skin anatomic barrier, which limits deeper penetration of drugs. Groundbreaking drug delivery systems, based on nanoparticles (NPs), have received much attention due to their ability to improve solubility, bioavailability, diffusion, targeting to specific types of cells, and limiting the secondary effects of the drugs employed in the treatment of AD. Even so, additional studies are still required to recognize the toxicological characteristics and long-term safety of NPs. This review discusses the current classical pharmacotherapy of AD against new nanoparticle skin delivery systems and their toxicologic risks.